2006
DOI: 10.1086/509517
|View full text |Cite
|
Sign up to set email alerts
|

A Common Haplotype of the Glucokinase Gene Alters Fasting Glucose and Birth Weight: Association in Six Studies and Population-Genetics Analyses

Abstract: Fasting glucose is associated with future risk of type 2 diabetes and ischemic heart disease and is tightly regulated despite considerable variation in quantity, type, and timing of food intake. In pregnancy, maternal fasting glucose concentration is an important determinant of offspring birth weight. The key determinant of fasting glucose is the enzyme glucokinase (GCK). Rare mutations of GCK cause fasting hyperglycemia and alter birth weight. The extent to which common variation of GCK explains normal variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
95
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(115 citation statements)
references
References 47 publications
18
95
1
1
Order By: Relevance
“…The BHS is a very comprehensively phenotyped resource, with the selected cohort having been followed up on average four times over 21 years with multiple metabolic measures, and thus was well-suited to addressing the aim of this study. Our cross-sectional association analyses confirmed previous findings of associations between the GCK rs1799884 variant and raised fasting glucose levels [9,22], the APOA5 rs662799 and rs3135506 variants and raised triacylglycerol levels [16,17,34], and the LPL rs328 variant and reduced triacylglycerol levels and raised HDL-C levels [20,21].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The BHS is a very comprehensively phenotyped resource, with the selected cohort having been followed up on average four times over 21 years with multiple metabolic measures, and thus was well-suited to addressing the aim of this study. Our cross-sectional association analyses confirmed previous findings of associations between the GCK rs1799884 variant and raised fasting glucose levels [9,22], the APOA5 rs662799 and rs3135506 variants and raised triacylglycerol levels [16,17,34], and the LPL rs328 variant and reduced triacylglycerol levels and raised HDL-C levels [20,21].…”
Section: Resultssupporting
confidence: 89%
“…There have been many crosssectional studies of such genotype-phenotype associations in individuals of different ages [6][7][8][9][10]; however, these studies do not test the possible longitudinal effects of variants in the same individuals. Like the associated risks of many diseases, measures of quantitative traits of clinical relevance often alter with age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even more intriguing is the association of the protective allele at the same locus with prostate cancer [27], a coincidence that remains unexplained. Of the other MODY genes, large-scale association studies and meta-analyses have shown an association of the G-30A SNP in the GCK promoter with fasting glucose [25,26,28]. On the other hand, the previously reported association of the missense A45T SNP in NEUROD1 with type 2 diabetes has not been substantiated in a comprehensive meta-analysis [29].…”
Section: Monogenic Diabetesmentioning
confidence: 97%
“…Type 2 diabetes is a risk factor for development of cardiovascular disease, but increased fasting glucose at non-diabetic levels also increases risk of cardiovascular events [9]. Several loci have been shown to influence this variable [10][11][12][13][14][15][16][17]. Recently, the international Meta-Analysis of Glucose and Insulin-related Trait Consortium (MAGIC) collaboration engaged in a large meta-analysis of data from 21 GWAS and identified novel loci influencing fasting glucose homeostasis.…”
Section: Introductionmentioning
confidence: 99%